Building Islamic Fintech Ecosystems in Indonesia - Afrizal (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
This study aims to explore how to build a fintech ecosystem that contributes to the progress of Sharia fintech in Indonesia. This research uses a literature review about the fintech ecosystem and the main actors who interact and collaborate within it. The study results show that the Major Ecosystem forms a solid foundation for the development of the Sharia fintech industry in Indonesia. Collaboration between Sharia fintech platforms, Sharia banks and other partners enables the adoption of Sharia principles in increasing the accessibility and sustainability of financial services. Meanwhile, the Minor Ecosystem complements and strengthens efforts in building the Sharia fintech industry. With collaboration between regulators, fatwa institutions, industry associations and educational institutions, the Sharia fintech industry can continue to develop and make a positive contribution to financial inclusion and inclusive economic growth.